JURIDICAL ANALYSIS OF HUMANITARIAN FUNDS MANAGEMENT OF PHILANTHROPIC INSTITUTIONS IN INDONESIA CASE STUDY OF FUNDS DETERMINATION IN ACT: JURIDICAL ANALYSIS OF HUMANITARIAN FUNDS MANAGEMENT OF PHILANTHROPIC INSTITUTIONS IN INDONESIA CASE STUDY OF FUNDS DETERMINATION IN ACT - Firman, Muhammad Syafry; Isman, Isman; Muthoifin, Muthoifin (Mendapo: Journal of Administrative Law, 2023)
Islamic philanthropy has a significant role in helping to address socioeconomic problems in society and overcoming poverty. With humanitarian and disaster issues, the Action of Quick Response is one of the most trusted Islamic Philanthropic Institutions for the community to manage the funds of the people to be channeled to those who are entitled to receive it. But in recent years, there have been several cases of humanitarian funding deviations reported in the mass media. One of the most controversial cases is the alleged, deviation of humanitarian funds for personal benefit by the Quick Action Response agency’s leadership. Quick Action Response is alleged to have used humanitarian funds provided for the benefit of personal entities, and illicit activities (terrorism) and is not in accordance with its designation. Legal analysis is conducted with a qualitative descriptive, approach method used namely normative juridical approaches, and data collection in this study with library research. The Research results show that the management of humanitarian funds gathered by the Quick Action Response is contrary to Law Number 23 of 2011 on zakat, as Quick Action Response raises humanitarian funds by name of Zakat, Infaq, and Shodaqoh but is not managed under the provisions of the Zakat Act.